Job Location Decisions and the Effect of Children on the Employment Gender Gap - Andrea Albanese; Adrián Nieto; Konstantinos Tatsiramos (Global Labor Organization (GLO), 2022)
We study the effect of childbirth on local and non-local employment dynamics for both men and women using Belgian social security and geo-location data. Applying an eventstudy design that accounts for treatment effect heterogeneity, we show that 75 percent of the effect of the birth of a first child on the overall gender gap in employment is accounted for by gender disparities in non-local employment, with mothers being more likely to give up non-local employment compared to fathers. This gender specialisation is mostly driven by opposing job location responses of men and women to individual, household and regional factors. On the one hand, men do not give up non-local employment after childbirth when they are employed in a high-paid job, have a partner who is not participating in the labour market or experience adverse local labour market conditions, suggesting that fathers trade off better employment opportunities with longer commutes. On the other hand, women give up non-local jobs regardless of their earnings level, their partner's labour market status and local economic conditions, which is consistent with mothers specialising in childcare provision compared to fathers.
Keywords: J13; J16; J61; C21; C23; J22; R23; 330; gender gap; childbirth; job location; cross-border employment; specialisation